The Hugo masters an anthology of Chinese classical music - Jiang Xianwei; Yan Tieming (Celestial Harmonies, 1992)
Western classical music, for all its richness, covers just several hundred years. China's classical music, by comparison, covers several thousand years. To condense that vast treasury of music into four volumes was a serious undertaking. Here is the glorious result. [Booklet]
Keywords: CD